Technical-tactical analysis of wrestling competitions in 2016 Rio Olympic Games - Arabaci, R.; Sahin, S.; Cicioglu, I. (Journal of Physical Education Research, 2018)
The aim of study was to analyze technical-tactical and scores of the free-style wrestling competitions at the Summer Olympic Games in Rio, Brazil in 2016. Video analysis of a total of 141 matches (n = 119 wrestlers) in 6 weight categories in 35 countries was conducted with the Dartfish Connect Plus 8.0 program. The technical points, winning types, applied techniques, distribution of points were examined according to weight categories and total. Independent Samples t-test and One Way ANOVA tests were used to compare the data. Bonferroni test was used in the binary comparisons. The results indicated that the average duration of the wrestling match was 319.2 ± 93.1 sec. It was determined that there was a statistical difference according to the match duration (F = 3.55). 33.6% of the technical points were 1 point, 61% were 2 point and 5.4% were 4 point. 666 points in the first and 640 points in the second period (p.0.05). In the wrestling matches, were found that the most applied techniques were back pass takedown n = 179, push to out n = 125, passive n = 82, leg tackle n = 77, gut wrench n = 72 and double leg tackle n = 26, respectively. As a result, in the XXXI. Summer Olympic Games in Rio, freestyle wrestling match durations were different according to the weight categories, the most achieved technical points were 2 point and the most winnings are achieved with points. It was determined that the most back pass takedown and push to out techniques. It can be said that the changes made in wrestling rules have positive effects in terms of wrestling attractiveness and dynamism.